1996
DOI: 10.1002/masy.19961100107
|View full text |Cite
|
Sign up to set email alerts
|

Crystaf: Crystallization analysis fractionation. A new approach to the composition analysis of semicrystalline polymers

Abstract: Crystallization Analysis Fractionation is a new technique for the analysis of composition distribution in semicrystalline polymers; more specifically for the analysis of branching distribution in Polyethylene and tacticity in Polypropylene type resins. CRYSTAF as well as TREF (Temperature Rising Elution Fractionation) are separation techniques which fractionate species of differing crystallizability by slow cooling of a polymer solution. TREF however, demands in addition to the crystallization step a second te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 4 publications
2
48
0
Order By: Relevance
“…1,2,11 It has been shown that CRYSTAF and TREF results are similar. However, one of the advantages of CRYSTAF is that the analysis time is much shorter than the one required by TREF.…”
Section: Crystallization Analysis Fractionation-crystafsupporting
confidence: 51%
“…1,2,11 It has been shown that CRYSTAF and TREF results are similar. However, one of the advantages of CRYSTAF is that the analysis time is much shorter than the one required by TREF.…”
Section: Crystallization Analysis Fractionation-crystafsupporting
confidence: 51%
“…By monitoring the polymer solution concentration during crystallization, the cumulative and differential SCBD can be obtained without the need to physically separate the fractions. CRYSTAF produces similar results to TREF but in a shorter time and with a simplified apparatus [7][8][9] . Much effort has been focused on the relationship between the structure of active sites and microstructure of polymer chains because of the very broad range of product applications [10][11][12] .…”
Section: Introductionsupporting
confidence: 75%
“…Copolymer microstructure was analyzed by 13 C NMR according to the method reported by Randall 14) . CRYSTAF measurements were carried out as described in the literature 8) .…”
Section: Polymerization and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fractionation principle of this technique is already published in the literature [33][34][35]. The sample solution of concentration 0.1% (w/w) was prepared in 1, 2, 4 trichlorobenzene (TCB) at 160°C under stirring for 60 min.…”
Section: Copolymer Composition Distributionmentioning
confidence: 99%